Oilseed flax cultivation: optimizing phosphorus use for enhanced growth and soil health - He, Ning; Huang, Fang; Luo, Dingyu; Liu, Zhiwei; Han, Mingming; Zhao, Zhigang; Sun, Xian (Frontiers in Plant Science, 2024)
Oilseed flax (Linum usitatissimum L.) yields are phosphate (P) fertilizer-limited, especially in the temperate semiarid dryland regions of North China. However, there are limited studies on the effects of P-fertilizer inputs on plant growth and soil microorganisms in flax planting systems. To address this gap, a field experiment was conducted with four treatments: no P addition and application of 40, 80, and 120 kg P ha⁻¹, respectively. The aim was to investigate the influence of various P fertilizer inputs on yield, plant dry matter, P use efficiency, as well as the population of soil arbuscular mycorrhizal fungi (AMF) and bacteria in dryland oilseed flax. Our results show that the P addition increased the dry matter, and the yield of oilseed increased by ~200% at 120 kg P ha -1 addition with inhibition on the growth of AMF hyphae. The moderate P supply (80 kg ha -1 ) was adequate for promoting P translocation, P use efficiency, and P recovery efficiency. Soil pH, available P, and available K significantly (p < 0.05) promoted the abundance of the dominant taxa (Acidobacteria_GP6, Sphingobacteria and Bacteroidetes). In addition, it is imperative to comprehend the mechanism of interaction between phosphorus-fertilizer inputs and microbiota in oilseed flax soil.This necessitates further research to quantify and optimize the moderate phosphorus supply, regulate soil microbes to ensure high phosphorus utilization, and ultimately establish a sustainable system for oilseed flax cultivation in the local area.